2023
DOI: 10.1039/d2nj04939b
|View full text |Cite
|
Sign up to set email alerts
|

Dual dielectric-responsive hybrid materials with fluorescent properties

Abstract: Organic-inorganic hybrid perovskite (OIHP) materials have received extensive attention from the scientific community because they have shown vigorous vitality and broad exploration space in the fields of photovoltaic, light-emitting diodes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Compared to other transition metal ions Zn 2+ and Cu 2+ , Mn-based organic–inorganic hybrid halides not only have the advantage of low raw material cost but also exhibit a unique tunable luminescent color, making them an emerging material with fascinating optical, electronic, mechanical, and other properties. By selecting appropriate organic and inorganic components, three-dimensional (3D), two-dimensional (2D), one-dimensional (1D), and zero-dimensional (0D) structures can be obtained. Compared to high-dimensional materials, low-dimensional (0D/1D) hybrids have a higher exciton binding energy and generation energy, thus exhibiting excellent luminescence efficiency and stability. Generally, tetrahedral-coordinated Mn 2+ emits green light, while octahedral-coordinated Mn 2+ emits red light. , As an example, Chen et al reported that the 0D Mn-based hybrid (PPh 4 ) 2 MnBr 4 displays efficient green emission and successfully prepared organic light-emitting diodes, indicating outstanding electroluminescent properties of the material .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other transition metal ions Zn 2+ and Cu 2+ , Mn-based organic–inorganic hybrid halides not only have the advantage of low raw material cost but also exhibit a unique tunable luminescent color, making them an emerging material with fascinating optical, electronic, mechanical, and other properties. By selecting appropriate organic and inorganic components, three-dimensional (3D), two-dimensional (2D), one-dimensional (1D), and zero-dimensional (0D) structures can be obtained. Compared to high-dimensional materials, low-dimensional (0D/1D) hybrids have a higher exciton binding energy and generation energy, thus exhibiting excellent luminescence efficiency and stability. Generally, tetrahedral-coordinated Mn 2+ emits green light, while octahedral-coordinated Mn 2+ emits red light. , As an example, Chen et al reported that the 0D Mn-based hybrid (PPh 4 ) 2 MnBr 4 displays efficient green emission and successfully prepared organic light-emitting diodes, indicating outstanding electroluminescent properties of the material .…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] Chiral spirocyclic amines are assembled with manganese halide to form 0D structures, which usually have excellent PL properties due to their strong quantum limiting effect. 24,27,41,42 In this work, we selected the protonated chiral spirocyclic organic ammonium R/S-HASD (HASD = 2-hydroxy-5-azaspiro-[4.5]decan) as a cation and the inorganic manganese bromide (MnBr 2 ) as inorganic frameworks, two new 0D organic-inorganic hybrid compounds (R/S-HASD) 2 MnBr 4 was prepared successfully. By differential scanning calorimetry (DSC) and dielectric measurements, it can be found that the two crystal samples underwent a plastic reversible phase transition near 380 K respectively, which results in the switchable behavior of the two compounds in the dielectric/SHG/PL physical channels.…”
Section: Introductionmentioning
confidence: 99%
“…34–40 Chiral spirocyclic amines are assembled with manganese halide to form 0D structures, which usually have excellent PL properties due to their strong quantum limiting effect. 24,27,41,42…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic hybrid perovskites (OIHPs) have become a research hotspot of functional materials due to the high-probability structural phase transition (SPT). The phase transitions are changes in internal molecular stacking patterns resulting in relevant physical properties changing or generating, such as dielectric. , Consequently, the SPT process induced by thermal stimulation is one of the key factors to realize the functionalization of materials. As well known, rare-earth (RE) possess excellent optical properties and abundant coordination modes . Thus, it is an effective strategy for achieving the multifunctional response by introducing the RE into OIHPs with phase transition, whereas it is few to combine phase transition and reversible SCSC transformation …”
Section: Introductionmentioning
confidence: 99%